Teacher’s Strategies to Internalize Religious Culture During Online Learning in Elementary School - Rohmah, Atifatur (EDUCARE: Journal of Primary Education, 2023)
This study aims to determine the implementation and strategies of educators in educating religious culture during learning at BISMA DUA elementary school at Kutisari Surabaya. The method used in this research is a qualitative approach with a type of field research. Data collection technique uses the Analysis Interactive Model from Milles and Huberman wich consist of data condensation, data presentation and drawing conclusions. The validity of the data using technique, source and time triangulation. The result of this study indicate that the strategies used by educators in inculcating religious culture online learning include; habituation strategies, internalization of religious values and special activities. While the method of cultivating religious culture used is knowing (knowledge), living (modelling) and religious ativities.